Origins and consequences of hyperosmolar stress in retinal pigmented epithelial cells - Willermain, François; Libert, Sarah; Motulsky, Elie; Salik, Dany; Caspers, Laure; Perret, Jason; Delporte, Christine (Frontiers in Physiology, 2014)
The retinal pigmented epithelium (RPE) is, composed of retinal pigmented epithelial cells joined by tight junctions and, represents the outer blood-retinal barrier (BRB). The inner BRB is made of the endothelial cells joined by tight junctions and glial extensions surrounding all the retinal blood vessels. One of the functions of the RPE is to maintain an osmotic transepithelial gradient created by ionic pumps and channels, and avoiding paracellular flux. Under such physiological conditions, transcellular water movement follows theis osmotic gradient and is flowingflows normally from the retina to the choroid through the RPE. Several diseases, such as diabetic retinopathy, are characterized by the BRB breakdown leading to leakage of solutes, proteins and fluid from the retina and the choroid. The prevailing hypothesis explaining macular edema formation during diabetic retinopathy relies onincriminates the inner BRB breakdown resulting in increased osmotic pressure leading in turn to massive water accumulation that can affect vision. Under these conditions, it has been hypothesized that RPE is likely to be exposed to hyperosmolar stress at its apical side. This review summarizes the origins and consequences of osmotic stress in the RPE. Ongoing and further research advances will clarify the mechanisms, at the molecular level, involved in the response of the RPE to osmotic stress and delineate potential novel therapeutic targets and tools.